(3GdRNGQa GdfHGJjg aj YeGFQ GdGSQI GdYdhjI HeOjfI GdbGgQI (B:s (3OQGSI CKQjI hafjI (B/s - (3,f``S```````Qjf eGg`````Q eM``eO GHQGg``````jes; (3GHh GdMeO eMehO aQZdjs; (3eMehO eQSj eQSjs (2024)
(3eQJ eOjfI GdbGgQI HGdYOjO ef GdeQGMd GdJGQjNjI GdJj CKQJ aj JchjfgG GdeYeGQj hGdRNQai MJi CUHMJ edjFI HcfhR ef GdRNGQa GdfHGJjI HGdefTCJ GdOjfjI hGdeOfjI hGdNjQjI hGdJi JYHQ Yf GdYXeI hGdKQGA aj GdYfGUQ GdRNQajI GdfHGJjI aJfhYJ GdRNGQa GdfHGJjI ai YUQ GdCSQI GdYdhjI JfhYG cHjQG aefgG eMGci ddWHjYI , heLQOI Yf GdWHjYI , hHGdZ GdafGfhf aj ESJNOGegG MJi hUagG GdHYV HCfgG eMGhdI dQSe UhQI GdLfI GdehYhOI aj GdbQCf GdcQje (B.(3hCNjQG XghQ cdkG ef CSdhH GdHGQhc hGdQchch GdChQHj hJCKjQgeG Ydi GdRNGQa GdfHGJjI ai YeGFQ CSQI eMeO Ydi heRL GdCSdhHGf eY GdCSdhH GdJQcj GdJbdjOj hEfJGL CfeGW RNQajg afjg YKeGfjI ChQHjI egLfg ef GdQchch hGdHGQhc GdYKeGfi ,GdJi EfOeLJ ajgG GdRNGQa GdfHGJjI eY YfGUQ RNQajI CNQi cQShe GdWjhQ, hGdCSeGc hGdbhGbY hGdQShe GdMjhGfjI (B.s
Cairo has gone through many historical stages that have influenced its architectural and decorative formation, making it rich with treasures of botanical decorations in religious, civil, and charitable buildings. These decorations reflect grandeur and wealth in their botanical elements. During the era of the Allawia family, botanical decorations varied significantly. Some imitated nature, while others were abstracted from it. Artists excelled in their use, and some even described it as an attempt to depict the promised paradise as described in the Holy Qur'an.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B509-533.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3RNGQa GdHGQhc hGdQhchchs; (3GdRNQaI GdfHGJjIs -- (3GdCQGHjScs -- (3RNQaI GdQheis